THE TRANSLATION ANALYSIS OF IDIOM IN FRIDAY NIGHT LIGHTS MOVIE SUBTITLE(A DESCRIPTIVE STUDY IN TERMS OF TYPES OF IDIOMS AND TRANSLATION STRATEGIES) - Dhea Adrian, - (2011)
The paper entitled 'The Translation Analysis of Idiom in Friday Night Lights Movie Subtitle (A Descriptive Study in Terms of Types of Idioms and Translation Strategies)' was aimed to find out types of idioms mostly used in subtitle of movie Friday Night Lights, as well as translation strategies mostly applied in translating the types of idioms. The paper was written based on a research on 200 sample of idioms which were taken from the movie subtitle. This research applied Hockett's theory of types of idioms to categorize the idioms chosen as sample of research and Baker's theory of translation strategies to find out the translation strategies of the idioms. Based on the data analysis, the research found that figure of speech (41%) was the most dominant type of idiom found in the movie subtitle. Meanwhile, translation by paraphrase (55%) was the most frequent translation strategy applied in the movie subtitle. The strategy was used mainly in translating figure of speech (63 items). Translation by paraphrase was considered as one of the best strategies in translating the figure of speech in the subtitle. The strategy was succes to deliver adequate comprehension of how figure of speech supposed to mean to the audience of the movie.